Production of antibodies to human interferons in mice. - Dalton, B J (1978)
Neutralizing antibodies were raised in mice that had been inoculated repeatedly with moderate quantities of human leukocyte interferon highly purified by affinity chromatography on immobilized anti-interferon globulins. Interferon preparations of lesser purity sensitized the mice to subsequent inoculations of interferon and almost invariably caused death before anti-interferon titers developed. Antibody-purified interferon stabilized by sodium dodecyl sulfate was a superior antigen to interferon that had received mouse serum albumin as an additive. The amount of antibody could be augmented by experimental induction of ascites. The antibodies specifically neutralized leukocyte and lymphoblastoid interferons but not those interferons obtained cultures of human foreskin fibroblasts, embryonic kidney cells, and amnion cells.